Finance for Food Towards New Agricultural and Rural Finance - Köhn, Doris (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book reflects the current state of discussion about agricultural and rural finance in developing and transition countries. It provides insight into specific themes, such as commodity value chains, farm banking, risk management in agricultural banking, structured finance, crop insurance, mobile banking, and how to increase effectiveness in rural finance. Case studies illustrate various aspects of agricultural and rural finance in developing economies. The book is based on one of the yearly financial Sector Development Symposia held by the KfW Development Bank.